Anti-money laundering in a nutshell awareness and compliance for financial personnel and business managers - Sullivan, Kevin (Apress, 2023)
Money laundering is endemic. As much as 5 percent of global GDP (USD3.6 trillion) is laundered by criminals each year. It's no wonder that every financial institution in the United States must comply with complex requirements mandated by a welter of federal anti-money laundering (AML) laws. Financial institutions and businesses that unknowingly serve as conduits for money laundering are no less liable to prosecution and fines than those that condone or abet it. This new edition will update the topics discussed, and introduce the changes and updates including information on the AMLA Act of 2020, new EU standards and directives, anti-money laundering on digital currencies, human and wildlife trafficking and more Author Kevin Sullivan draws on a distinguished career as an AML investigator and consultant to teach personnel in financial institutions and law enforcement what money laundering is, who does it, how they do it, how to prevent it, how to detect it, and how to report it in compliance with federal law. He traces the dynamic interplay among employees, regulatory examiners, compliance officers, fraud and forensic accountants and technologists, criminal investigators, and prosecutors in following up on reports, catching launderers, and protecting the integrity and reputations of financial institutions and businesses. Highly rated on Amazon and a Top 10 ranked book on Compliance, Anti-Money Laundering in a Nutshell is a concise, accessible, and practical guide to compliance with anti-money laundering law for professionals who are required, under penalty of hefty fines, to get anti-money laundering training.
Online resource; title from PDF title page (SpringerLink, viewed December 15, 2023)
Keywords: Money laundering -- Prevention -- United States; Money laundering -- Law and legislation -- United States